Ecological engineering : principles and practice. - Kangas, Patrick C., ....- (Boca Raton : CRC, 2004)
Less expensive and more environmentally appropriate than conventional engineering approaches, constructed ecosystems are a promising technology for environmental problem solving. Graduate students need an introductory text that details the biology and the ecology of this rapidly developing discipline, known as ecological engineering. Ecological Engineering: Principles and Practice fills this need by describing ecological concepts and theory and demonstrating their application to constructed ecosystems. Designed as a textbook for a semester length graduate-level course, the text introduces the major concepts and methods of ecological engineering along with this new discipline's most important real-world applications: treatment wetlands, microcosms, composting systems, restoration ecology, soil bioengineering, and invasive species control. The text surveys the field with an introductory chapter on definitions and principles, six chapters treating major sub-fields, a chapter on applications of economics, and a conclusion chapter with synthetic propositions with comments on education and future directions.